Confocal Raman microspectroscopy for spatially resolved tissue characterisation of disease-linked spectra-pathological signatures - Valous, Nektarios A.; Zörnig, Inka; Jäger, Dirk (Clinical and translational medicine, 2025)
Raman spectroscopy is a versatile analytical technique for highly specific molecular characterisation of cells, biofluids and tissues. Confocal Raman microspectroscopy combines optical microscopy with Raman spectroscopy to spatially resolve biochemical changes in tissue samples. This work focuses on research articles that utilise confocal Raman microspectroscopy in human or murine tissue sections for identifying disease-linked spectra-pathological features. For scientists and clinicians who seek ideas in incorporating confocal Raman microspectroscopy into their experimental workflows, this piece provides a curated selection of studies (spanning cancer and cardiovascular diseases) that highlight key spectroscopic and biomedical insights. The lack of standardisation and the fragmentation of research protocols are major challenges that limit study reproducibility and prevent systematic cross-validation. Moving forward, confocal Raman microspectroscopy, coupled with robust computational approaches, will continue to detect disease-specific spatiotemporal biomolecular signatures, and integration with complementary imaging or omics methods will keep enhancing its ability to analyse complex biological systems and uncover disease progression mechanisms. Key points Confocal Raman microspectroscopy enables spatially resolved tissue characterisation and reveals disease-linked spectra-pathological features. Key challenges limit clinical translation, for example, lack of standardisation and insufficient reference spectral databases. Future research progress depends on interdisciplinary collaboration, robust computational methods and integration with complementary imaging or omics technologies for enhanced disease characterisation.
Online veröffentlicht am 25. September 2025
Gesehen am 27.01.2026